2008
DOI: 10.1510/icvts.2008.184275
|View full text |Cite
|
Sign up to set email alerts
|

Lung perfusion during cardiac surgery with cardiopulmonary bypass: is it necessary?

Abstract: Thirty-two pigs were randomized into group I (aortic cross clamping, antegrade cardioplegia, moderate hypothermia) and group II (normothermia, beating empty heart). Groups were subdivided into subgroups A, B and C, receiving no lung perfusion, perfusion with arterial blood and perfusion with venous blood. Swan-Ganz catheter was used to take mean pulmonary artery pressure which would be used as lung perfusion pressure. Cardiopulmonary bypass (CPB) was established through cannulating aorta and double venae cavae… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
17
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(17 citation statements)
references
References 13 publications
0
17
0
Order By: Relevance
“…The authors found that in this cohort of patients managed with low levels of PEEP (4 [2. [2][3][4][5], median ), the utilization of low tidal volumes (below 8 ml/kg of predicted body weight) were associated with increased mortality. This suggests that low PEEP levels should not be associated with low tidal volumes….…”
Section: Positive End-expiratory Pressurementioning
confidence: 97%
See 2 more Smart Citations
“…The authors found that in this cohort of patients managed with low levels of PEEP (4 [2. [2][3][4][5], median ), the utilization of low tidal volumes (below 8 ml/kg of predicted body weight) were associated with increased mortality. This suggests that low PEEP levels should not be associated with low tidal volumes….…”
Section: Positive End-expiratory Pressurementioning
confidence: 97%
“…Several mechanisms are potentially involved and include ischemia-reperfusion phenomena, ventilation disorders or overload-related lung injury due to transfusion or early respiratory mechanics impairment (1)(2)(3)(4). Systemic inflammation due to ECC and aggressive high tidal volume ventilation can cause non-cardiogenic pulmonary edema or other organ failure (5)(6)(7).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Gabriel et al [19] demonstrated experimentally the advantages of the pulmonary trunk with controlled perfusion pressure using both arterial and venous blood. From the hemodynamic point of view, these authors observed a significant reduction in mean pulmonary artery pressure and pulmonary vascular resistance in the immediate postoperative period in animals that underwent perfusion controlled of the pulmonary trunk.…”
Section: Discussionmentioning
confidence: 99%
“…Techniques and principles of controlled lung perfusion are analyzed, based on recent research devised by Gabriel at al. 1 This section provides original discussions on extracorporeal circuit pathways for lung perfusion, how to determine lung perfusion pressure, lung perfusion using arterial and venous blood, and impact of controlled lung perfusion from hemodynamic, gasometric, inflammatory, and radiologic standpoint of view during heart surgery with CPB.…”
mentioning
confidence: 99%